1999
DOI: 10.1523/jneurosci.19-12-04907.1999
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities in Neuronal Process Extension, Hippocampal Development, and the Ventricular System of L1 Knockout Mice

Abstract: In humans, mutations in the L1 cell adhesion molecule are associated with a neurological syndrome termed CRASH, which includes corpus callosum agenesis, mental retardation, adducted thumbs, spasticity, and hydrocephalus. A mouse model with a null mutation in the L1 gene (Cohen et al., 1997) was analyzed for brain abnormalities by Nissl and Golgi staining and immunocytochemistry. In the motor, somatosensory, and visual cortex, many pyramidal neurons in layer V exhibited undulating apical dendrites that did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
185
1
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(201 citation statements)
references
References 67 publications
10
185
1
2
Order By: Relevance
“…Our results confirm a morphological phenotype previously observed in animal models (Dahme et al, 1997;Cohen et al, 1998;Demyanenko et al, 1999), but also presents an additional component in the human mutant neuron's reduced ability to generate APs.…”
Section: Discussionsupporting
confidence: 91%
“…Our results confirm a morphological phenotype previously observed in animal models (Dahme et al, 1997;Cohen et al, 1998;Demyanenko et al, 1999), but also presents an additional component in the human mutant neuron's reduced ability to generate APs.…”
Section: Discussionsupporting
confidence: 91%
“…Our examination of the published L1 Ϫ/Ϫ and CHL1 Ϫ/Ϫ phenotypes suggested that L1 Ϫ/Ϫ defects are much more severe than the mild axon guidance errors of the BACE1 null. L1 Ϫ/Ϫ mice exhibit severe brain deformities, including hypoplasia of the hippocampus, corticospinal tract, corpus callosum, cerebellar vermis, enlarged ventricles, and various behavioral abnormalities (47)(48)(49). However, CHL1 Ϫ/Ϫ and BACE1 Ϫ/Ϫ phenotypes appear nearly indistinguishable (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…L1 Ϫ/Ϫ mice have hydrocephalus, enlarged ventricles, and severe hypoplasia of certain CNS structures (e.g. hippocampus, corpus callosum, corticospinal tract, and cerebellar vermis) (47)(48)(49), whereas CHL1 Ϫ/Ϫ mice exhibit relatively mild axon mis-targeting in the hippocampus and olfactory bulb (31,32). Because L1 Ϫ/Ϫ abnormalities are markedly more serious than those of BACE1 null, it appeared less likely that abrogation of BACE1 cleavage of L1 could be responsible for the axon guidance defects of the BACE1 Ϫ/Ϫ mice.…”
Section: Bace1 ϫ/ϫ Hippocampal Mossy Fibers Have Reducedmentioning
confidence: 99%
“…Two different lines of mice lacking L1 have distinct developmental defects that display a reduced corticospinal tract and corpus callosum, exhibit less sensitivity to pain, enlarged ventricles, and errors in the topographical mapping of retinal axons in the superior colliculus (Cohen et al, 1997;Dahme et al, 1997;Demyanenko et al, 1999;Demyanenko and Maness et al, 2003).…”
Section: Nih Public Accessmentioning
confidence: 99%
“…Wild-type (L1+/+) and L1 mutant (Y/-; B6;129S7-L1cam tm1Sor ; Cohen et al, 1997) mice originally obtained from both Dr. Vance Lemmon (University of Miami, Miami, Florida) and Jackson Labs were maintained as a breeding colony at UCLA and genotyped as reported in Demyanenko et al (1999). Adult mice underwent unilateral, extradural dorsal rhizotomies as previously described in rats, although the deafferentation spanned from T10-L2 instead of the T12-L4 levels used previously (Runyan et al, 2005).…”
Section: Experimental Procedures Animals and Surgical Proceduresmentioning
confidence: 99%